PENGARUH KUALITAS PELAYANAN DAN KEPUASAN TERHADAP LOYALITAS WISATAWAN YANG BERKUNJUNG KE BOUNTY DISCOTHEQUE DI LEGIAN KUTA, BADUNG, BALI - Kalyana Puthujjana, Adhika Sugato; Suardana, I Wayan; Karini, Ni Made Oka (Jurnal Analisis Pariwisata, 2021)
This research is conducted to find out the relationship between service quality towards satisfaction and loyalty in Bounty Discotheque in Legian, Kuta, Badung, Bali. The sampling technique used is a purposive sampling technique. Data is collected by observation, interview and 5 point Linkert scale questionnaire. The questionnaire was distributed to 140 tourists visiting Bounty Discotheque. The instrument is validated using SPPS version 2.1 to check the validity, reliability with its Cronbach Alpha Coeficien value. The validity value for the whole component of the instrument was above 0.3 as the standard value for the validity. The reliability value is 0,909 which is higher than the standard value 0.60. The data was analysed using partial least square – structural equation modeling (PLS-SEM). Based on the analysis with PLS-SEM on bootstrapping with significance of 5 percen degree of degree of freedom (DF) = number of data – 2 = 138 is 1,977 (t Table) that the result is that the relationship value between quality service toward is 19,332, the value relationship between quality service toward satisfaction is 9.533 and the relationship value between satisfaction and loyalty is 3.034. The value of t Statistics of those three variable is higher than the t Table (19.332; 9.533; 3.034 > 1.977). Therefore, it can be concluded that there is a significance relationship between quality service toward satisfaction, there is a significance relationship between quality service toward loyalty and there is a significance relationship between satisfaction toward loyalty.